Hypoglycemic effects of space‐induced Lactobacillus plantarum SS18‐5 on type 2 diabetes in a rat model. Issue 9 (16th August 2021) - Yang, Feiyu; Wang, Jiyu; Zhang, Hongxing; Xie, Yuanhong; Jin, Junhua; Liu, Hui; Pang, Xiaona; Hao, Hongwei
Abstract: Probiotics can improve dyslipidemia and promote metabolic control as a therapeutic approach for type 2 diabetes mellitus (T2DM). The hypoglycemic effects of space‐induced Lactobacillus plantarum SS18‐5 on T2DM were explored in 4‐week‐old male Sprague Dawley rats. The normal (N) group was fed a basal diet, while the other groups received a high glucose fat diet. T2DM was established by streptozotocin injection and the T2DM rats were randomly divided into three groups, a diabetic (D) group (T2DM rats treated with saline only), GS18 group (T2DM rats treated with 10 9  CFU/ml of L. plantarum GS18), and SS18‐5 group (T2DM rats treated with 10 9  CFU/ml of L . plantarum SS18‐5). After continuous gavage for 6 weeks, blood biochemical indices were measured and livers were collected for histopathological examination. The colon contents were collected for counting of Escherichia coli, Clostridium perfringens, and Lactobacillus sp. The results showed that L. plantarum SS18‐5 effectively controlled the weight of rats, reduced levels of fasting blood glucose, glycosylated hemoglobin, and insulin, increased liver glycogen levels, improved abnormal metabolism of blood lipids, enhanced the effect of anti‐lipid peroxidation, alleviated chronic inflammation and fatty liver disease, and regulated the intestinal microbiota by reducing the numbers of E. coli and C. perfringens, and increasing the numbers of Lactobacillus sp. From these results, we conclude that space‐induced L . plantarum SS18‐5 has the potential to improve T2DM by alleviating hypoglycemia and regulating the intestinal microbiota. Practical applications: With the exploration of the universe, a large number of studies have observed the changes of microorganisms in space flight, which provided a new method for high‐quality microbial pharmaceuticals in the space environment. In this study, the space environment mutated. Lactobacillus plantarum SS18‐5 can effectively improve the blood glucose of rats with type 2 diabetes, relieve oxidative stress, reduce blood lipid content, enhance immune capacity, and regulate intestinal microflora, which has potential use in the treatment of type 2 diabetes.